Threat, voting and candidate support. The impact of mortality salience - Bäck, Hanna; Carroll, Royce; Knapton, Holly; Renström, Emma A. (Frontiers in Political Science, 2023)
How does threat motivate political choices? An extensive literature has noted the importance of threat in influencing political behavior. A growing literature in political psychology has used the concept of ‘mortality salience’ to examine the role of existential threat in political decisions. Scholars have argued that inducing mortality salience by asking individuals to think about their own death should result in either reinforcement of existing political worldview, a shift to a more politically conservative view, or support for a ‘status quo’ option more generally. In a survey experiment (N = 484) performed one week before the 2016 US Presidential election we find that mortality salience led to an increased likelihood of voting for Hillary Clinton, particularly for moderate and independent respondents. In a second experiment (N = 1514) manipulating mortality salience, participants were presented with a fictive candidate varying in experience level (representing the status quo or change) and partisanship. The results showed that independent participants preferred the status quo candidate under mortality salience. We interpret the findings in both studies as supporting a connection between threat and preference for the status quo in psychological terms, at least for less partisan voters, rather than a conservative shift in ideological terms or a tendency to reinforce existing views.